Schools must provide nonacademic services to students with disabilities. Issue 10 (June 2018) - Charmatz, Marc
Abstract : Title II of the Americans with Disabilities Act applies to public entities, including state and community colleges. Section 504 of the Rehabilitation Act applies to programs and activities receiving federal financial assistance. Virtually all colleges and universities receive federal financial assistance, and "all of the operations of" a school are subject to Section 504. Most of the case law has focused on admission and expulsion, academic adjustments, auxiliary aids and services, and testing. See 34 C.F.R. 104.44. However, schools are also required to ensure nondiscrimination in nonacademic services — housing, health insurance, counseling, financial aid, physical education and athletics, recreation, transportation, and extracurricular activities. See 34 C.F.R. 104.43.